Kapasitas Pemerintah Daerah Dalam Penanggulangan Bencana Gempa dan Tsunami di Kepulauan Mentawai - Afdal Rizki; Roni Ekha Putera; Ilham Adelano Azre (Institut Pemerintahan Dalam Negeri, 2020)
Disaster risk management sector has become a serious concern for the government due to various disasters that have occurred in recent years followed by many issues came up.This study aims to describe and analyze the capacity of Local Government of Mentawai Islands in organizing disaster affairs in the region. This study is motivated by the vulnerability of Mentawai Islands to earthquakes and tsunamis because the islands are just above the subduction zone.The study applied a qualitative approach with descriptive design by data collection through interviews, observations, and documents.The study concluded that the capacity of Local Government of Mentawai Islands Regency in the implementation of disaster management still needs improvements. It can be proven that there are still some programs that haven’t run optimally. In general, the biggest obstacles are budget constraints, limited supporting infrastructure for disaster management in the regions, and geographical conditions of Mentawai Islands.